The universal structure of categories : towards a formal typology - Wiltschko, Martina (Cambridge : Cambridge University Press, 2014)
Using data from a variety of languages such as Blackfoot, Halkomelem, and Upper Austrian German, this book explores a range of grammatical categories and constructions, including tense, aspect, subjunctive, case and demonstratives. It presents a new theory of grammatical categories - the Universal Spine Hypothesis - and reinforces generative notions of Universal Grammar while accommodating insights from linguistic typology. In essence, this new theory shows that language-specific categories are built from a small set of universal categories and language-specific units of language. Throughout the book the Universal Spine Hypothesis is compared to two alternative theories - the Universal Base Hypothesis and the No Base Hypothesis. This valuable addition to the field will be welcomed by graduate students and researchers in linguistics.
The universal structure of categories -- A history of ideas behind the spine -- The universal spine as a heuristic for the identification of grammatical categories -- Anchoring categories in independent clauses -- Anchoring categories in dependent clauses -- Nominal anchoring categories -- Categories that introduce a point of view -- Towards a formal typology.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Categorial grammar; Structural linguistics; Language, Universal